EFEKTIVITAS PENGELOLAAN DANA ZAKAT PROFESI DI LAZISMU KABUPATEN PANGKEP - islamiah (JURNAL ILMIAH EDUNOMIKA, 2025)
This study aims to analyze the effectiveness of professional zakat fund management at LAZISMU in Pangkep Regency. Professional zakat is a type of zakat maal that has emerged in response to the dynamics of the modern economic structure, where individual income sources stem from professional occupations such as employees, medical personnel, educators, and other similar professions. This research adopts a qualitative approach using descriptive methods, relying on in-depth interviews, field observations, and document analysis. The study focuses on three key aspects in measuring effectiveness: institutional transparency and accountability, the accuracy of zakat distribution to beneficiaries (mustahik), and the sustainability of empowerment programs implemented. The findings indicate that the management process of professional zakat by LAZISMU Pangkep has been relatively optimal; however, it still faces challenges such as the low level of public education and understanding of professional zakat, as well as the underutilization of a digital-based reporting system.